HOW TO WIN AN ARGUMENT (Author: Michael A. Gilbert) - Carson, A. S. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1980)
Michael A. Gilbert. HOW TO WIN AN ARGUMENT. Toronto: McGraw-Hill, 1979. 173 pp. $5.98.